Peptide inhibitors of HIV-1 protease and viral infection of peripheral blood lymphocytes based on HIV-1 Vif - Potash, Mary Jane (The National Academy of Sciences, 1998)
We recently reported that HIV-1 Vif (virion infectivity factor) inhibits HIV-1 protease in vitro and in bacteria, suggesting that it may serve as the basis for the design of new protease inhibitors and treatment for HIV-1 infection. To evaluate this possibility, we synthesized peptide derivatives from the region of Vif, which inhibits protease, and tested their activity on protease. In an assay of cleavage of virion-like particles composed of HIV-1 Gag precursor polyprotein, full-length recombinant Vif, and a peptide consisting of residues 21–65 of Vif, but not a control peptide or BSA, inhibited protease activity. Vif(21–65) blocked protease at a molar ratio of two to one. We then tested this peptide and a smaller peptide, Vif(41–65), for their effects on HIV-1 infection of peripheral blood lymphocytes. Both Vif peptides inhibited virus expression below the limit of detection, but control peptides had no effect. To investigate its site of action, Vif(21–65) was tested for its effect on Gag cleavage by protease during HIV-1 infection. We found that commensurate with its reduction of virus expression, Vif(21–65) inhibited the cleavage of the polyprotein p55 to mature p24. These results are similar to those obtained by using Ro 31–8959, a protease inhibitor in clinical use. We conclude that Vif-derived peptides inhibit protease during HIV-1 infection and may be useful for the development of new protease inhibitors.